Gênero e política: o feminino como antítese da sociedade capitalista na teoria crítica de Herbert Marcuse - Jucá, Mikaelly da Costa (2023)
The main aim of this dissertation is to present the women's movement as a revolutionary force and antithesis to the one-dimensional society in Herbert Marcuse's critical theory. The focus here is on the issue of gender, which will be developed from the conception of feminism as a catalyst for changes in social dynamics. Despite one-dimensio nal society's attempts to contain any forces of opposition, especially with the predominance of repressive desublimation and its integrating character that further reinforces female oppression in class society. Among the catalyzing agents, the philosopher sees the women's movement as a radical power for change, women as a revolutionary force and as the constituent of a political movement of contestation necessary for a new princip le of reality. Marcuse, like Angela Davis, in her essay Marxism and Feminism, which we will use as one of our main references, recognizes the potential of the women's movement and proposes the possibility of a new sociability, when the current form of social relations in which the male-female dichotomy predominates would be overcome. A controlled desublimation could lead to a new sociability, which will only be possible with a new sensibility, with the transformation of sexuality into Eros. We can conclude that, for Marcuse, female emancipation should not be seen as an unattainable utopia, but as a political struggle that has all the possible means to take place; it may be difficult and painful, but it is a necessary process for achieving a mature society for both men and women. The struggle for women's emancipation is also a struggle for human emancipation.